1990
DOI: 10.1111/j.1699-0463.1990.tb01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackie B1 virus infection enhances the bacterial invasiveness, the phagocytosis and the membrane permeability in HEp‐2 cells

Abstract: To analyze the effect of coxsackie B1 virus infection on bacterial in vasiveness, phagocytosis and cytoplasma membrane permeability, we have studied invasiveness of Shigella flexneri, unspecific phagocytosis of latex particles and release of the non‐metabolizible amino acid, α‐aminoisobutyric acid (AIB). Virus infection enhanced invasiveness of S. flexneri and phagocytosis of latex beads and increased plasma membrane permeability as measured by release of AIB. The effect on all three functions increased with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…5). Although many viral infections result in a decrease in macrophage functions, including phagocytosis, some viruses, such as herpes simplex virus (2), Coxsackie virus (22), or Newcastle disease virus (19), have been shown to enhance the ability of these cells to incorporate various targets. Whereas contradictory results have been reported after LDV infection (17,18,32), another nidovirus, mouse hepatitis virus, can also increase macrophage-mediated phagocytosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…5). Although many viral infections result in a decrease in macrophage functions, including phagocytosis, some viruses, such as herpes simplex virus (2), Coxsackie virus (22), or Newcastle disease virus (19), have been shown to enhance the ability of these cells to incorporate various targets. Whereas contradictory results have been reported after LDV infection (17,18,32), another nidovirus, mouse hepatitis virus, can also increase macrophage-mediated phagocytosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has also been observed that coinfections of HEp-2 cells with enteroviruses and Campylobacter isolates resulted in an increase of bacterial invasion (Konkel and Joens 1990). Coxsackievirus B 1 has also been reported to induce an enhancement of invasion of Shigella flexneri in HEp-2 cells, which correlated with an increase of induced phagocytosis (Modalsli et al 1990). Recently, we observed an increase in invasion ability of S. flexneri in different cell lines infected with poliovirus or other enteroviruses (Marchetti et al 1992;Seganti et al 1994).…”
Section: Introductionmentioning
confidence: 98%
“…This enhancement can be divided into two phases: an early and a late phase. The early phase enhancement, up to 3 h after inoculation, can be reproduced by pretreating cells with UVinactivated virus (12) and is not dependent on protein synthesis (15). In contrast, the late phase effect, 6 h after virus inoculation, requires viable virus (12) and coincides with protein synthesis (15).…”
mentioning
confidence: 97%
“…Cellular alterations induced by viral infections have a significant effect on the ability of bacteria to adhere to and invade cells. Several investigators have demonstrated that virus infection results in an increase in bacterial adherence (6,7,16) and invasiveness (7,12). Infection of HEp-2 cell cultures with coxsackie B1 virus enhanced the invasiveness of Shigella flexneri (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation